Dampak Pendidikan Pesantren terhadap Moral Bermasyarakat Santri Pondok Pesantren Tashilul Huda Kauman, Wiradesa, Pekalongan - Atqia, Wirani; Zuhriyah, Aminatuz (el-Tarbawi, 2021)
The ever increase of moral degradation cases has proven the inability of Indonesian modern educational institutions to create students with good character. On the contrary, Islamic boarding school educational institutions are one of the institutions that are expected to be able to change the morals of the community, especially students to socialize through programs, regulations, and habits of students in Islamic boarding schools. This study aims to see the impact of the Taslihul Huda Islamic Boarding School education on the morals of the santri community through existing activities, programs, and regulations. The researcher used interviews and observations to find data from the head and boarding school administrators, the community, and the students who were there, then the researchers analysed and processed the data by triangulation. From the results of the study, it can be said that the existing programs and regulations at the Taslihul Huda Islamic boarding school are effective in shaping the morals of the santri and the community's ability to provide positive responses to students in engaging with the community. Keywords: Islamic Boarding School; Morality; Society; Students